2016
DOI: 10.3746/pnf.2016.21.4.384
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Strawberry, Korean Raspberry, and Mulberry Extracts on Human Ovarian Cancer A2780 Cells

Abstract: Reactive oxygen species are tumorigenic by their ability to increase cell proliferation, survival, and cellular migration. The purpose of the present study was to compare the antioxidant activity and cytotoxic effects of 3 berry extracts (strawberry, Korean raspberry, and mulberry) in A2780 human ovarian carcinoma cells. Except for raspberry, the ethyl acetate or methylene chloride fractions of berries containing phenolic compounds exerted dose dependent free radical scavenging activities. In the raspberry fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This observation suggests that even more research, such as the current study, is needed to evaluate the therapeutic utility and safety of polyphenolic compounds. CHSP is more effective in inhibiting ovarian cancer cell proliferation than paeonol [ 19 ] or extracts of strawberry, Korean raspberry, and mulberry [ 20 ]. The lower cell viabilities demonstrate that CHSP has high potential for the prevention and therapy of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that even more research, such as the current study, is needed to evaluate the therapeutic utility and safety of polyphenolic compounds. CHSP is more effective in inhibiting ovarian cancer cell proliferation than paeonol [ 19 ] or extracts of strawberry, Korean raspberry, and mulberry [ 20 ]. The lower cell viabilities demonstrate that CHSP has high potential for the prevention and therapy of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies revealed that regular consumption of fruits and vegetables improve overall human health and wellbeing by preventing noncommunicable diseases including several types of cancer (Siddiqui et al, 2010;Rajput and Mandal, 2012;Brown, 2012 andLee et al, 2016). The biological value of fruits and vegetables depends upon presence of bioactive constituents, especially those of antioxidant and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…In endometrial cancer cell lines urolithin A obtained from black raspberries was found particularly effective in suppressing cell proliferation in a time-and dose-dependent manner, arresting the G2/M phase of the cell cycle and modulating ERa-dependent gene expression, thereby inhibiting endometrial cancer proliferation (Zhang et al, 2016). Raspberry extracts promoted anticancer activities also in human ovarian carcinoma (Kim et al, 2016, Lee et al, 2016aLee et al, 2016b), breast (Wang et al, 2013;Zhang et al, 2015;Wang, Zhu, and Marcone 2015;Ljevar et al, 2016;Park et al, 2017) and cervical cancer cells (Saini et al, 2014;Ljevar et al, 2016) as demonstrated by the reduction in cell viability and promotion of apoptotic and cytotoxic processes. Interesting results were also obtained in vulvar squamous cell carcinoma cell line, where black raspberry extract treatment efficiently upregulated caspase-14 level, suggesting its possible use in topical treatment of vulvar lesions (Joehlin-Price et al, 2014).…”
Section: Raspberry and Cancermentioning
confidence: 99%